PENGARUH MENDONGENG TERHADAP PERKEMBANGAN KARAKTER SISWA DI KELAS IV SD 043950 SIGARANG-GARANG - Enjelika Br Ginting; Anton Sitepu; Dyan Wulan Sari HS; Bogor Lumbanraja; Heka Maya Sari; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the influence of storytelling on the development of student character at SD Negeri 043950 Sigarang-garang for the 2023/2024 academic year. Namely, to find out the characteristics, language style and content of the message conveyed by the researcher through fairy tales. This research starts from the emergence of awareness for every child to convey values ​​that have the essence of character values. The storytelling method is also considered to provide good and useful understanding. Therefore, the presentation using the fairy tale method is what makes researchers interested in examining the characteristics, language style and content of the message conveyed in fairy tales. In this study, a quantitative survey type method was used, the population of this study was class IV students at SD Negeri 043950 Sigarang-garang. Sampling was taken using saturated sampling and the sample used was 30 students. The results of this research show that the correlation test results can be seen in the correlation coefficient value r_count ≥r_tabel or r_(count) of (803) ≥r_tabel (2.042), so it can be concluded that the alternative hypothesis (Ha) is accepted, namely that there is a negative influence between storytelling (X ) on the development of student character (Y) class IV at SD Negeri 043950 Sigarang-garang.. It can also be seen from the results of the t test where r_count ≥r_tabel, namely t_(count ) (7.126) and t_table of 2.042. If we consult the t_table value at degrees of freedom (df) = 30, it is 2.042, so that t_count is 7.126≥ t_tabel 2.042, so that t_count ≥ t_tabel, which means that Ha is accepted, meaning there is a negative influence of storytelling (X) on the development of students' character (Y).